[OP.7B.03] THE EFFECTS OF LCZ696 ON LEFT VENTRICULAR REMODELING IN HYPERTENSIVE PATIENTS – RESULTS OF A DOUBLE BLIND, RANDOMIZED, MULTICENTER TRIAL. (September 2017) - Ott, C.; Wagner, F.; Mayr, M.; Delles, C.; Keicher, C.; Aichner, S.; Khder, Y.; Yates, D.; Albrecht, D.; Langenickel, T.; Freyhardt, P.; Janka, R.; et al.
Abstract : Objective: Arterial hypertension and the resulting reduction in aortic distensibility impose increased hemodynamic load to the left ventricle and, if untreated may lead to left ventricular hypertrophy (LVH) and heart failure. We analyzed the effects of LCZ696 on LV-structure and function as well as on regional and global aortic distensibility. Design and method: We conducted a prospective, randomized, double-blind, parallel-group, multicenter study in 114 patients with mild to moderate hypertension. Patients were randomized to LCZ696 200/400 mg o.d. or olmesartan (OLM) 20/40 mg o.d. At baseline, 12 and 52 weeks left ventricular mass (LVM) index as well as local and global aortic distensibility were evaluated by 3 T magnetic resonance imaging (MRI) and pulse wave analysis, respectively. Results: Baseline characteristics, office BP (155.1 ± 9.0/92.2 ± 8.7 mmHg) and LVM index (72 ± 15 g/m 2 ) were similar between treatment groups at baseline. After 52 weeks of treatment, decrease in office systolic BP was greater in the LCZ696 group than in the OLM group (−4.99 [95% CI −9.46 to −0.53] mmHg, p = 0.029). Compared to OLM, treatment with LCZ696 resulted in a greater decrease in LVM index at 12 weeks (−4.05 [95% CI −7.9 to −0.2] g/m 2, p = 0.039) and at 52 weeks (−3.27 [95% CI −6.2 to −0.34] g/m 2, p = 0.029). After adjustment for office SBP at follow-up, the change in LVM index at 12 weeks (p = 0.0356) and at 52 weeks (p = 0.0189) remained significantly greater in the LCZ696 group. Local aortic distensibility measured by MRI in the ascending, proximal and distal descending aorta did not show any significant difference between groups. LCZ696 was associated with a larger decrease of central pulse pressure compared to OLM (−3.50 [95% CI: −6.15 to −0.85] mmHg, p = 0.01) at 52 weeks. Both treatments were safe and well tolerated. Conclusions: In patients with hypertension, LCZ696 reduced LVM to significantly greater extent than OLM. Since reduction of LVM is associated with improved cardiovascular prognosis, the observed effect of LCZ696 on LVM is of clinical relevance.